UBUNTU AS FOREIGN POLICY: THE AMBIGUITIES OF SOUTH AFRICA'S BRAND IMAGE AND IDENTITY (The Strategic Review for Southern Africa, 2021)
South Africa's 2011 White Paper on foreign policy, "Building a Better World", is predicated on the far-reaching ambition of how Ubuntu (humanity) and Batho Pele (putting people first) together with their underlying humanist principles will guide the country's external relations. However, while noble, this calculus is poorly conceived as an approach to global issues. The article argues that while still a relatively successful nation brand if measured by marketing indicators, South Africa's normative currency and agency in foreign policy has depreciated considerably, with a direct bearing on its nation brand and identity. These are examined with regard to the security of citizens and the personality of the state and provide a register of the branding and image deficits of the White Paper. Such deficits are then considered in terms of the cosmopolitan vision in South Africa's foreign policy and its moral and normative underpinnings. The article provides examples in both the domestic and global regimes to demonstrate the extent to which South Africa has lost its normative resilience in the conduct of its foreign policy, thus giving rise to ambiguities in its brand image and identity.